THE GROWTH OF THE CONTROLLER AND THE BUSINESS ADMINISTRATION CURRICULUM. - Lay, Chester F. (The Accounting Review, 1928)
The organization of educational work has been viewed as a rapidly growing interest among accounting teachers in various business school across the U.S. Education in university schools of business is still in the experimental or possibly the transitional stage. These considerations underlie the proposition presented in this article, a proposition involving the way business is organizing for its work, the way an educational program in business is organized, and the problem of correlating business and educational organization, with special reference to the part which may and should be played by university teachers of accounting. It has been assumed for this discussion that the purpose is to train men who will eventually become responsible business executives or such professional techniques as public accountants. A separate study of controllership as a program in accounting would seem desirable for two distinct purposes. First, it would add the usual accounting training. The second purpose for which controllership may be studied is to serve as a unifying, organizing course for all business administration students.